Background emotional experiences - VILIŪNAS, V. (Psichologija, 1997)
The article discusses one aspect of emotional interaction, namely, the influence of already existent emotional states on the rise of situational emotions. Three cases of such influence were distinguished: l) the development of emotions from sentiment; 2) the dependence of emotions on mood; and 3) the development of emotions from feelings (in the Wundtian sense). Interpretation of feelings in W. Wundt’s conception is extensively discussed.